PENGARUH PEMBERIAN BERBAGAI LEVEL KALSIUM DAN FOSFOR PADA PAKAN TERHADAP KEKUATAN BIOMEKANIK DAN KADAR MINERAL TULANG TIBIA ITIK TURI - , Herlina Umbu Deta, Dr. drh. Irkham Widiyono ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The experiment was conducted to study the effects of various levels of calcium (Ca) and phosphorus (P) in the diets of biomechanical strength and mineral content (calcium and phosphorus content) in tibia bone of Turi ducks. The experimental design used Completely Randomized Design (CRD) 3x3 factorial. Each of groups consited of 10 female and 1 of male duck gived feeding containing three levels of calcium (2,75, 3,25 and 3,75%) and three levels of phosphorus (0,25, 0,35 and 0,45%) and there were combination of 9 treatment. Each cage was fed one combination level of calcium and phosphorus. Each of treatment contains 3 replication, each totaling 27 experiment units (the unit of observation). After 36 weeks one duck of treatment was taken per treatment per group, killed to excised the right tibia. Samples tibia was measured of the biomechanical strenght and mineral content. Biomechanical strenght by bone bending test using Universal Testing Machine (Tokyo, Ltd). Bone mineral content such as calcium content were analyzed using by Atomic Absorption Spectrometer (AAS)(USA, Ltd) and phosphorus content with Spectrophotometri methods. All data were analyzed statistical using Analize of Variance (ANOVA) used by SPSS 17,0. The results showed that the tibia bone on the biomechanical strength of Turi ducks affected by level of phosphorus in the diets (P <0.05). The value of P levels (0.35 and 0.45%) was higher than bending from lower levels of phosphorus in the diets (0.25%). Bone mineral content didnât influenced by the levels of calcium and phosphorus in the diets (P>0.05). Phosphorus content in the feeding was determined on the biomechanical strength (physical) in tibia bone of Turi duck.